2015
DOI: 10.1007/s10722-015-0285-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic diversity among Jordanian wild barley (Hordeum spontaneum) genotypes revealed by SSR markers

Abstract: Wild barley, Hordeum spontaneum is the progenitor of cultivated barley. The center of diversity is in the Fertile Crescent in the Near East, where wild barley grows under a wide range of environmental and climatic conditions. Jordan wild barley is expected to harbor important genes that could be used for the improvement of the cultivated varieties especially in their tolerance to drought. To assess genetic diversity and allelic variation of Jordanian wild barley, 103 wild barley genotypes collected from differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
3
8
2
Order By: Relevance
“…These variations showed some limitations such as phenotype modifications due to environmental influence, when compared with molecular markers (Ferreira, 2006). The SSR molecular markers are known to be efficient for genetic diversity studies of pearl millet (Mariac et al, 2006;Bashir et al, 2015;Shakhatreh et al, 2015). The current study showed a lower average (4.071) number of alleles per locus compared to that reported by Mariac et al (2006) which was 6.2 for 421 cultivated accessions from Niger, and 16.4 for accessions from a wide geographic range in West and Central Africa (Stich et al, 2010).…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…These variations showed some limitations such as phenotype modifications due to environmental influence, when compared with molecular markers (Ferreira, 2006). The SSR molecular markers are known to be efficient for genetic diversity studies of pearl millet (Mariac et al, 2006;Bashir et al, 2015;Shakhatreh et al, 2015). The current study showed a lower average (4.071) number of alleles per locus compared to that reported by Mariac et al (2006) which was 6.2 for 421 cultivated accessions from Niger, and 16.4 for accessions from a wide geographic range in West and Central Africa (Stich et al, 2010).…”
Section: Discussioncontrasting
confidence: 47%
“…Most of the differentiation (95%) was present within accessions. This could be due to the natural selection and gene flow as it had been reported in many studies (Turpeinen et al, 2003;Nevo et al, 2004;Shakhatreh et al, 2015). According to Nevo et al (1998), natural selection appears to be a major differentiating and orienting force of regional evolutionary change, maintaining genetic polymorphisms under conditions of environmental heterogeneity and stress.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The wide diversity observed in this region could be due to selection of unconsciously appropriate alleles by farmers with better adaptation to local climatic conditions. In pea, as in other organisms, selection appears to be a major differentiating and orienting force of regional evolutionary change, maintaining genetic polymorphisms under conditions of environmental heterogeneity and stress (Hübner et al, 2009;Shakhatreh et al, 2016). In the present study, except for two samples, no marker heterozygosity was detected, suggesting that these landraces were highly homozygous.…”
Section: Discussioncontrasting
confidence: 44%
“…They indicate that all compounds show only moderate activity. Many chalcones are known to exhibit reasonable antibacterial activity due to the presence of ,-unsaturated carbonyl groups that can enhance activity (Shakhatreh et al, 2016). Out of the various synthesized compounds, it is observed that chalcone (C1), with phenyl and p-methylphenyl moieties, proved to be the most effective against all strains with a zone of inhibition of 12 mm.…”
Section: Antibacterial and Dpph Scavenging Activitiesmentioning
confidence: 99%